(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this article, we analyzed the genesis of a memory policy that achieves repair of the work files of public servants who were di- sappeared and/or murdered buy the last military dictatorship in Argentina. Decree No 1199, signed on July 2012 by the former President Cristina Fernandez de Kirchner, ordered their survey and documentary repair, indicating in each one the true cause of the termination of employment. To that end, we investigated the background of this policy from democratic transition and, particularly, we chose a concrete case to how it worked. From the documentary appended in the mentioned decree, the case of Silvia Emilia Miguens, worker in the Buenos Aires Customs Office is especially relevant, since not only she was abducted from her workplace but history shows us the scope of complicity of the employer with the repressive system.